2005
DOI: 10.1007/s10551-005-0869-x
|View full text |Cite
|
Sign up to set email alerts
|

The Pragmatic and Ethical Barriers to Corporate Social Responsibility Disclosure: The Nike Case

Abstract: Numerous studies have documented the demand for information regarding corporations' relationships to society. Much recent research has demonstrated why stakeholders need this information, and how it benefits both companies and the public. These studies suggest numerous methods by which companies can effectively disclose corporate social responsibility (CSR) information to the public, but in practice, reporting this type of information is fraught with legal and ethical uncertainty often unexplored in most liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 17 publications
2
55
0
2
Order By: Relevance
“…Thus, corporate social responsibility practice is often cited as one of the most important factor influencing company performance. A review of the literature suggested that corporate social responsibility effort may improve the performance of a company [3]- [5]. This study extends previous studies by addressing the associations between corporate social responsibility practice and new product development performance.…”
Section: Literature Review and Research Hypothesessupporting
confidence: 65%
“…Thus, corporate social responsibility practice is often cited as one of the most important factor influencing company performance. A review of the literature suggested that corporate social responsibility effort may improve the performance of a company [3]- [5]. This study extends previous studies by addressing the associations between corporate social responsibility practice and new product development performance.…”
Section: Literature Review and Research Hypothesessupporting
confidence: 65%
“…For example, exposure of companies such as Nike (e.g. DeTienne and Lewis, 2005) and Primark (e.g. Jones et al, 2009) in the 1990's and more recently Apple (Garside, 2013) for use of child labour and sweatshops in Asian manufacturing sites, caused negative press and unwanted attention from stakeholders, leading to tarnished reputations and public condemnation of their actions.…”
Section: Sustainability In the Construction Industrymentioning
confidence: 99%
“…Prior studies on organisational legitimacy threats focus on the analysis of corporate narrative documents, including press releases, annual reports and CSR reports (e.g., Ogden and Clarke, 2005;Linsley and Kajüter, 2008;De Tienne and Lewis, 2005;Castelló and Lozano, 2011). Stakeholder communications relating to violations of social norms and rules or stakeholder values and beliefs are treated as part of the organisational context which is described in order to shed light on corporate reporting (e.g., Hooghiemstra, 2000).…”
Section: Introductionmentioning
confidence: 99%